Legal Protection for Consumers Against Adulterated Fuel Causing Motor Vehicle Damage - Prastiya, David Eka; Iskandar, Hardian (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2025)
This study aims to analyze the forms of legal protection for consumers who suffer losses due to the use of adulterated fuel and to examine the legal liability of business actors within the framework of consumer protection law in Indonesia. The research employs a normative legal research method using statutory, conceptual, and literature-based approaches. Primary legal materials include the Consumer Protection Law, the Oil and Gas Law, and relevant provisions of civil law. The analysis is conducted qualitatively through systematic interpretation of legal norms and doctrines. The findings indicate that legal protection for consumers is provided through preventive and repressive mechanisms. Adulterated fuel is classified as a defective product that gives rise to strict liability under the Consumer Protection Law as well as liability for unlawful acts under the Civil Code. However, law enforcement remains suboptimal due to weak supervision, limited institutional capacity, and evidentiary difficulties faced by consumers. This study recommends strengthening preventive supervision through random fuel quality testing, increasing the effectiveness of sanctions, enhancing the institutional capacity of the Consumer Dispute Resolution Agency (BPSK), and simplifying the burden of proof for consumers to ensure legal certainty and effective consumer protection.